TECHNOLOGICAL INNOVATION AND HUMAN CAPITAL: UNVEILING ITS ROLE IN ENHANCING ISLAMIC BANK PERFORMANCE - Zakiy, Faris Shalahuddin; Agriyanto, Ratno; Farida, Dessy Noor; Rahmiyanti, Firdha; Wijayanti, Provita; Fajriatussaadah, Nurul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to examine how technological capital affects financial performance and investigate the moderating role of human capital efficiency in this relationship. This study is analyzed using panel data estimation techniques obtained from the financial statements of Islamic banks in Indonesia for 2013-2024. We also performed a robustness check using alternative control variable. The results indicate that technological capital does not significantly enhance the performance of Islamic banks. In the moderating relationship, human capital efficiency moderates the relationship between technological capital and financial performance. Islamic banks should focus on optimizing the use of technological innovations to provide easier public access to services. Furthermore, Islamic banks must position their human resources as the driving force, ensuring that the adaptation, development, and implementation of technology remain in line with sharia principles.